ECOTOURISM AS A LIVELIHOOD BOOST FOR COASTAL COMMUNITIES: ANALYSIS OF FIVE LIVELIHOOD CAPITAILS USING THE SUSTAINABLE LIVELIHOODS APPROACH ON LEMUKUTAN ISLAND - Musa, Pabali; Marini, Marini; Nursodik, Tabah; Mukhlisah, Rafikah; Winarsih, Sri; Wirayuda, Rangga (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study examines ecotourism as a lever for coastal community livelihood using the Sustainable Livelihood Approach (SLA) on Lemukutan Island, Bengkayang Regency. The purpose of the research is to analyze how ecotourism development is related to the five livelihood capitals of the community, namely natural, human, social, physical, and financial capital. The research was conducted with a qualitative approach through case studies, using in-depth interviews, participatory observations, and focus group discussions, and supported by secondary data from official reports and scientific literature. The results of the study show that ecotourism on Lemukutan Island makes a significant contribution to increasing household income, expanding employment, and developing local businesses based on homestays, MSMEs, and tourism services. In terms of natural capital, the marine ecosystem that is still maintained is the main attraction, despite facing pressure due to the increasing number of tourists. Human capital develops through the involvement of youth and women in tourism management, although the limitations of formal training remain an obstacle. Social capital is reflected in the practice of mutual cooperation and the role of tourism-aware groups, while physical and financial capital is shown through infrastructure improvements, distribution of clean water, electricity, and increased sources of community income. These findings confirm that SLAs are relevant to understanding the dynamics of livelihoods in ecotourism, as well as to providing recommendations for strategies to strengthen community capacity and manage resources in a sustainable manner.